2012
DOI: 10.1016/j.amjcard.2011.11.061
|View full text |Cite
|
Sign up to set email alerts
|

United States National Prevalence of Electrocardiographic Abnormalities in Black and White Middle-Age (45- to 64-Year) and Older (≥65-Year) Adults (from the Reasons for Geographic and Racial Differences in Stroke Study)

Abstract: A US national sample of 20,962 participants (57% women, 44% blacks) from the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study provided general population estimates for ECG abnormalities among black and white men and women. Participants were recruited during 2003–2007 by random selection from a commercially available nationwide list, with oversampling of blacks and persons from the stroke belt for a cooperation rate of 49%. Measurement of risk factors and 12-lead ECGs (centrally coded usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 11 publications
8
48
4
1
Order By: Relevance
“…In our study, prehypertension was not associated with major or minor ECG abnormalities. Using the REGARDS study cohort, Prineas et al reported a weak association of SBP (including normotension and prehypertension range) with prevalent major ECG abnormalities (OR 1.05); 17 however, in contrast to the current study, they did not adjust for a history of CHD, CV and lifestyle risk factors and HTN duration. One of the explanations for our current findings may be that the association of SBP with ECG abnormalities may only manifest at SBP levels above the prehypertension range.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In our study, prehypertension was not associated with major or minor ECG abnormalities. Using the REGARDS study cohort, Prineas et al reported a weak association of SBP (including normotension and prehypertension range) with prevalent major ECG abnormalities (OR 1.05); 17 however, in contrast to the current study, they did not adjust for a history of CHD, CV and lifestyle risk factors and HTN duration. One of the explanations for our current findings may be that the association of SBP with ECG abnormalities may only manifest at SBP levels above the prehypertension range.…”
Section: Discussioncontrasting
confidence: 80%
“…8,16-20 The association of both major and minor ECG abnormalities with traditional CV risk factors, including hypertension (HTN), has been previously reported. 17,21,24 …”
Section: Introductionmentioning
confidence: 99%
“…Two more recent cohort studies attempted to address this major confounder by drawing from a geographically diverse population. Prineas et al (30) analyzed ECGs obtained from participants in the Reasons for Geographic and Racial Difference in Stroke Study (REGARDS) cohort. Subjects were randomly recruited from across the United States.…”
Section: Bi-racial Cohorts Reporting J-point Amplitudementioning
confidence: 99%
“…This is consistent with the previously mentioned American study that evaluated electrocardiographic disorders in 20,962 people according to sex and age. 5 These abnormalities have been correlated with significantly higher risk of fatal coronary heart disease, 27 for which primary arrhythmia is the main mechanism. 28 This ECG disorder was more prevalent among women, and this might be explained by the significant influence of sex hormones on the QT interval in women: whereas this component is only shortened through the influence of testosterone in men, significant estrogen activity in women prolongs this interval while their progesterone acts similarly to testosterone.…”
mentioning
confidence: 99%